Restorative Justice in Rantau Prapat District Court for Oil Palm Theft Cases - Prayetno, Dwi; Tahir, Ach.; Siregar, Andalan (Yayasan Lembaga Studi Makwa, 2025)
This study examines the implementation of restorative justice in resolving oil palm theft cases at the Rantau Prapat District Court, Indonesia. The research is grounded in the increasing application of restorative approaches within Indonesia’s criminal justice system, particularly following regulatory reforms encouraging diversion and mediation in minor property crimes. Employing a normative-empirical method, this study combines statutory analysis with field data derived from court decisions, interviews with legal practitioners, and relevant secondary literature. The objective is to evaluate how restorative justice principles—such as victim-offender dialogue, restitution, community involvement, and proportional accountability—are applied in practice and to assess their effectiveness in achieving substantive justice. The findings reveal that restorative justice mechanisms in oil palm theft cases prioritize compensation, reconciliation, and social harmony over punitive imprisonment. In several cases, settlement agreements facilitated by judges and prosecutors resulted in restitution payments and formal apologies, leading to case dismissal or reduced sentencing. This approach has contributed to reducing case backlogs and prison overcrowding while promoting community-based conflict resolution. However, challenges remain, including inconsistencies in procedural standards, limited institutional guidelines, and disparities in judicial discretion. Additionally, concerns arise regarding power imbalances between plantation companies and economically vulnerable defendants. The study concludes that restorative justice at the Rantau Prapat District Court reflects a progressive shift toward a more humanistic and efficient criminal justice model. Strengthening regulatory clarity, institutional capacity, and safeguards for vulnerable parties is essential to ensure fairness, transparency, and sustainability in the application of restorative justice for property-related offenses in Indonesia.